Angular dependent FORC and FMR of exchange-biased NiFe multilayer films. (24th January 2017) - Gallardo, R A; Khanal, S; Vargas, J M; Spinu, L; Ross, C A; Garcia, C
Abstract: Dynamic ferromagnetic resonance (FMR, X-band 9.8 GHz) and static first-order reversal curve (FORC) techniques are combined to study the intrinsic exchange-bias distribution via measurements of in-plane angular variation in (FeNi/IrMn) n multilayers. The angular dependence of the exchange bias field was qualitatively and quantitatively investigated using both methods, which are sensitive to different couplings between the ferromagnetic layers. We have used the analysis of the angular dependence of first-order reversal curve (AFORC) data, extracted from FORC curves measured from 0 ∘ up to 360 ∘ in 10 ∘ steps. In addition, its counterpart angular dependence of FMR (AFMR) measurements were carried out and correlated with the AFORC results. The AFORC proved to be useful for simultaneously studying the magnetization reversal processes and magnetic interactions between the layers of the (FeNi/IrMn) n . These interactions are related to the structure and interfaces in the (FeNi/IrMn), and the results obtained by AFMR and AFORC are contrasted with a modified theoretical model for domain-wall formation.